Renoprotective Effects of Eugenol-loaded Chitosan Nanoparticles on Septic Rats - Qutb, Sarah Ali; Soliman, Amel Mahmoud; Fahmy, Sohair Ramadan; Mohamed, Ayman Saber (Drug Delivery Letters, 2025)
BackgroundSepsis is a severe medical disorder that poses a significant risk to life, leading to elevated rates of sickness and mortality globally, reaching 11 million annually. It is distinguished by an imbalanced immune response to infection, which subsequently causes failure in several organs. Eugenol is obtained from clove oil and possesses various beneficial properties, such as antifungal, anti-inflammatory, antiviral, antioxidant, anticancer, and antibacterial effects.AimsThe present study aimed to assess the effectiveness of eugenol-loaded chitosan nanoparticles (EC-NPs) in protecting against kidney damage caused by sepsis using the cecal ligation and puncture (CLP) model.MethodsThirty rats were divided into five groups: sham, sepsis, and septic rats treated with chitosan, eugenol, or EC-NPs.ResultsAdministration of EC-NPs dramatically enhanced renal function, as evidenced by the reduced urea, creatinine, and uric acid concentrations. Moreover, EC-NPs caused an elevation in glutathione reductase (GSH), glutathione-S-transferase (GST), superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT) in addition to decreasing the production of malondialdehyde (MDA) and nitric oxide (NO). EC-NPs administration reduced the DNA damage in septic rats and partially restored the aberrant structure of renal tissues in septic rats. Furthermore, the immunohistochemical examination showed a marked decrease in tumor necrosis factor-alpha (TNF-α) and interleukin-1 beta (IL-1β) expression.ConclusionIn conclusion, EC-NPs attenuated renal injury in septic rats through their anti-oxidant and anti-inflammatory activities and protection of DNA.
Keywords: Eugenol